Новый для науки циклоп (Crustacea, Cyclopidae) из Восточных Карпат и Предкарпатья - Монченко, В.И. (Вестник зоологии, 1980)
Аn illustrated description of a new subspecies Acanthocyclops (Megacyclops) viridis oligotrichus subsp. n. from wells of two districts is given. It differs from the type subspecies by almost complete absence of inner hair on furca, by lesser sizes of females (1700 mkm) and males (1240 mkm), by lengthened dorsal seta, that is neary equal to outer seta and is 86% of fureal length in females (and more than 100% in males) instead of 50—54% in type subspecies, by relation of innermost and outermost setae in females (2,8 instead of 2,0—2,2), by relation of inner middle seta to furca (6,4 instead of 4,0— 4,5) and by lengthened setae on distal endopod jont P₄ (these setae reach the end of api cal spines).